Magnetic fields. A Wiew of Peruvian science fiction from the 19th century to the present day - Güich Rodríguez, José (2017)
The article proposes a tour that explains the process of Peruvian science fiction, a cultural practice that until a few years ago was located in the peripheral areas of the literary system, almost silenced by the main currents markedly realistic. Recently it has emerged as a tradition that goes back to the founding novel of Julian of Portillo Lima de periods for what has gone through gender in our country: Modernism, Vanguard, Generation of 50, Decades of 1960 and 1970 and From 1980 to our days. In this way, an integrative perspective is built that also takes into account the relation of works and authors to the framework of both local and external production. It is thus demonstrated that in our country, science fiction was born independently of Western hegemonic centers, then, with its specificity, dialogue with the important development of this narrative and build an identity of their own.